Report of the committee appointed by the Honourable the Lord Provost and magistrates, Dean of Guild , and Deacon Convener, of Glasgow, to construct and verify dublicates of the imperial standards of weights and measures for that city, &c.&c ([s.n.], 1826)
Cover title reads: Report respecting weights and measures.